Beyond the Hype of Big Data Analytics Deployment: Conceptualization and Challenges Epistemology - Urus, Sharina Tajul; Othman, Intan Waheedah; Rasit, Zarinah Abdul; Bakar, Noraizah Abu; Nazri, Sharifah Nazatul Faiza Syed Mustapha (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Businesses, government sectors, academia and society have been flooded with data which nowadays have become valuable economic assets. Data and Big Data Analytics (BDA) are vital for the succession of any organization. Big Data Analytics (BDA) delineates the approaches utilized to examine, process, analyze and expose hidden underlying patterns, interesting relations, and intelligence from huge datasets for different purposes. Despite the growth and widespread use of data analytics, the study on this research area is still at the nascent stage. The scenario is seen particularly for the developing countries like Malaysia. Previous literature has recognized data analytic development and its effect but has not yet provided a comprehensive review. This paper intends to conceptualize BDA manifestation, its application, and its challenges epistemology. This study employs a comprehensive review of past literature to serve the purpose. The findings of this paper will enhance the understanding of BDA conception epistemology (definition and application). This concept paper also intends to shed some light on BDA research areas by identifying the challenges surrounding BDA deployment. From the theoretical point of view, this paper contributes to providing BDA taxonomy based on the application in various industries. From the practical perspective, this paper contributes to BDA research field by identifying the obstacles that need to be managed by the BDA adopter for optimum utilization and decision making. From the government perspective, it contributes to Malaysian national agenda to becoming a leading regional BDA solution hub for all sectors and developed nation by the year 2025.